2014
DOI: 10.1007/s00701-014-2217-3
|View full text |Cite
|
Sign up to set email alerts
|

Intractable occipital lobe epilepsy: clinical characteristics, surgical treatment, and a systematic review of the literature

Abstract: The management of OLE has been aided greatly by the availability of high-resolution diagnosis. Postoperative visual field deficits occur in a significant proportion of patients. Comprehensive intracranial EEG coverage of all occipital surfaces helps to define the epileptogenic area and preserve visual function, especially in cases of focal cortical dysplasia undetectable by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
3
41
0
3
Order By: Relevance
“…Another series reported that 57% of patients with parietal onsets achieved seizure freedom but 30% developed Gerstmann syndrome . A report of patients undergoing resections of occipital lobe seizure foci found that 71% were seizure‐free, but 39% reported new visual field defects . Although treatment with brain‐responsive neurostimulation is less likely to result in seizure freedom than treatment with epilepsy surgery, substantial seizure reductions were achieved and several patients achieved extended periods without seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another series reported that 57% of patients with parietal onsets achieved seizure freedom but 30% developed Gerstmann syndrome . A report of patients undergoing resections of occipital lobe seizure foci found that 71% were seizure‐free, but 39% reported new visual field defects . Although treatment with brain‐responsive neurostimulation is less likely to result in seizure freedom than treatment with epilepsy surgery, substantial seizure reductions were achieved and several patients achieved extended periods without seizures.…”
Section: Discussionmentioning
confidence: 99%
“…6 A report of patients undergoing resections of occipital lobe seizure foci found that 71% were seizure-free, but 39% reported new visual field defects. 28 Although treatment with brain-responsive neurostimulation is less likely to result in seizure freedom than treatment with epilepsy surgery, substantial seizure reductions were achieved and several patients achieved extended periods without seizures. Baseline assessments for the RNS System trials were limited to 3 months, and thus whether a patient had a prior history of extended periods of seizure freedom is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…7,19,20 Occipital Lobe Epilepsy Occipital lobe epilepsy is an uncommon clinical presentation, affecting 2% to 13% of those with focal epilepsies. 54 Occipital lobe epilepsy can arise due to recognized electroclinical syndromes, as well as symptomatic causes 55 ; however, seizures associated with mt.3243A > G MELAS and POLG have a clearly documented posterior predilection-particularly early in the disease course. 4,33,42…”
Section: Status Epilepticusmentioning
confidence: 99%
“…5 To minimize the likelihood for or extent of postoperative visual impairment, mapping techniques by means of electrocortical stimulation under awake conditions have been applied since the beginning of epilepsy surgery. 14 Nevertheless, although numerous case series with reports on outcome following resective surgery involving the occipital lobe exist, [1][2][3]7,8,10,14,18,21 only a few mention intraoperative mapping as an adjunct to preserve visual integrity. 3,14,21 In fact, the literature lacks detailed descriptions of the technique on how to perform visual electrocortical stimulation.…”
mentioning
confidence: 99%
“…14 Nevertheless, although numerous case series with reports on outcome following resective surgery involving the occipital lobe exist, [1][2][3]7,8,10,14,18,21 only a few mention intraoperative mapping as an adjunct to preserve visual integrity. 3,14,21 In fact, the literature lacks detailed descriptions of the technique on how to perform visual electrocortical stimulation. In his book Operative Techniques in Epilepsy, 5 Girvin briefly mentions the use of a visual board, which has been a well-established practice for awake perimetry testing at our institution and will be illustrated in the following case.…”
mentioning
confidence: 99%